Corporate Governance and Financial Performance: Case Study Banks in Turkey - Erben Yavuz, Asuman; Doğan, Mesut; Yazıcı, Ayşe Meriç (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The purpose of this paper is to identify the determinants of board size. In other words, it is aimed to determine the corporate governance variables and firm-specific internal factors that determine the board size of banks. For these purposes, the data of 10 banks whose stocks were traded in Borsa Istanbul (BIST) between 2010-2020 were used in the research. Balanced panel data analysis was used in the study. Unit root tests, cross-section dependence, heteroskedasticity tests, and White Period Standard Errors and Covariance Method were used in empirical analysis. According to the analysis results; there is a positive and statistically significant relationship between board size and return on assets, foreign board member ratio, supervisory board member ratio, duality, and total assets. On the other hand, there is a negative relationship between the size of the board of directors and the market value/book value, free float ratio, the capital share of the largest shareholder, the ratio of female and independent board members.